Cognitive-affective structure of gratitude and its relationships with subjective well-being. (October 2022) - Zhang, Linting; Zhu, Ningzhe; Li, Wenjie; Li, Chengcheng; Kong, Feng
Abstract: Gratitude is considered to be a multidimensional construct consisting of both cognitive (cognitive appraisals of benefaction) and affective (feelings of gratitude) components, which is crucial for health and well-being. However, few studies have examined the cognitive-affective structure of gratitude and its associations with subjective well-being. Thus, the present study explored the two-dimensional structure of gratitude and its predictive effects on subjective well-being. Study 1 showed that the bi-factor structure of gratitude had the best fit with the data compared with the one- and two-factor models, and both general and affective gratitude positively predicted subjective well-being at the cross-sectional level. Study 2 further found that general gratitude positively predicted life satisfaction and positive affect after 3 months. However, cognitive gratitude negatively predicted subjective well-being at both cross-sectional and longitudinal levels. Therefore, future gratitude studies should consider the two-dimensional structure of gratitude. Highlights: We tested the cognitive-affective structure of gratitude. The bi-factor model of gratitude fitted well. General gratitude predicted life satisfaction and positive affect at both cross-sectional and longitudinal levels. Affective gratitude positively predicted life satisfaction and positive affect cross-sectionally. Cognitive gratitude negatively predicted life satisfaction and positive affect at both cross-sectional and longitudinal levels.